2020
DOI: 10.3390/cells9010240
|View full text |Cite
|
Sign up to set email alerts
|

The Expanding Therapeutic Potential of Neuronal KCC2

Abstract: Dysfunctions in GABAergic inhibitory neural transmission occur in neuronal injuries and neurological disorders. The potassium–chloride cotransporter 2 (KCC2, SLC12A5) is a key modulator of inhibitory GABAergic inputs in healthy adult neurons, as its chloride (Cl−) extruding activity underlies the hyperpolarizing reversal potential for GABAA receptor Cl− currents (EGABA). Manipulation of KCC2 levels or activity improve symptoms associated with epilepsy and neuropathy. Recent works have now indicated that pharma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 131 publications
0
32
0
Order By: Relevance
“…This extensive study revealed the mechanisms involved in NKCC1 molecular transportation and communication and further provided insights into ion selectivity as well as coupling and translocation; a clearer framework for understanding the physiological functions of NKCC1 in relation to human diseases was also established [57]. Besides, modulation of NKCC1 activity alongside that of KCC2 has been implicated in the development and progression of HD [2,[58][59][60]. These CCCs are differentially expressed over the course of development, and so the activity of KCC2 and NKCC1 is not synonymous between immature and mature neurons [50].…”
Section: Introductionmentioning
confidence: 92%
See 4 more Smart Citations
“…This extensive study revealed the mechanisms involved in NKCC1 molecular transportation and communication and further provided insights into ion selectivity as well as coupling and translocation; a clearer framework for understanding the physiological functions of NKCC1 in relation to human diseases was also established [57]. Besides, modulation of NKCC1 activity alongside that of KCC2 has been implicated in the development and progression of HD [2,[58][59][60]. These CCCs are differentially expressed over the course of development, and so the activity of KCC2 and NKCC1 is not synonymous between immature and mature neurons [50].…”
Section: Introductionmentioning
confidence: 92%
“…Noteworthily, recent works have now potentially indicated that pharmacological enhancement of KCC2 function could reactivate dormant relay circuits in injured mouse and patient brain, leading to functional recovery and the amelioration of neuronal abnormality and disease phenotype associated with mouse and human models of neurological disorders including HD [58][59][60]86,88,89]. Indeed, there is a growing potential for KCC2 as a vital therapeutic target for neurological diseases and subsequent inhibitory input dysfunctions [60].…”
Section: Kcc2 Regulation and Function In The Hd Brainmentioning
confidence: 99%
See 3 more Smart Citations